TATA KOTA TRADISIONAL JAWA SEBAGAI PENUNJANG PARIWISATA DI KOTAGEDE YOGYAKARTA (Tinjauan Estetis) - Suratno Suratno (LIPI Press, 2003)
The aim of this research is to explore and examine the contribution of aesthetic dimension of Javanese traditional City plan in supporting tourism industry in Kotagede Yogyakarta. This is a combined research, which relies on both relevant library materials as well as field findings such as observation and interviews. Further, descriptive and interpretative analyses are employed. The findings of research indicates that Kotagede Yogyakarta still retains some elements of Javanese traditional city plan such as traditional market, town square, mosque complex equipped with graveyard, remnants of Javanese court, and housing compound. Those Kotagede's buildings were built with specifically Javanese positioning. The streets connecting the buildings cut the block in four-sided shapes. There are many aesthetic aspects of the Kotagede city plan that is potential for tourism industry. Among those aspects are the Kotagede's pristine and clean environment and the uniqueness of its old and traditional buildings. To add its esthetic aspects, Kotagede is widely well known as traditional Javanese city with all its elements, and as a center of silver crafting.